Psychologists and their theories for students - Krapp, Kristine M. (Gale virtual reference library, 2005)
Perfect for research assignments in psychology, science and history, this one-stop source for in-depth coverage of major psychological theories and the people who developed them provides a unique approach to the study of psychological history as it pertains to analysis. 2 volumes.